In Defence of Weinrib’s and Beever’s Interpretive Theories of Negligence - Allcock, Martin (LexisNexis Australia, 2017)
There have been a number of rights-based theories of private law which have emerged in recent years. Among these are the theories advanced by Ernest Weinrib and by Allan Beever, which, taken together, present a theory of negligence based on corrective justice and Kantian right. Weinrib’s and Beever’s rights-based theories have been the subject of much criticism, primarily for their use of rationalist and interpretive techniques of reasoning. This article serves two primary purposes. The first is to provide a summary of these criticisms and the responses to them, made primarily by Beever. The second is to advance further argument in response. The primary contention in this article is that the criticisms made of Weinrib’s and Beever’s interpretive theories are themselves arguably based upon theoretical assumptions which are not without controversy. It is suggested that future debate should focus on resolving the more fundamental theoretical issue as to what constitutes appropriate grounds of law.